PARTISIPASI MASYARAKAT MUSLIM BANDA ACEH DALAM PERAYAAN RITUAL PANGGHUNI UTHIRAM - Muhammad Muhammad (Prodi Studi Agama-Agama, 2021)
Participation of the Muslim community in the celebration of the Panghuni Uthiram Ritual (case study in Banda Aceh). In 2014, to be precise on Sunday, April 20 2014, the Hindus of Banda Aceh celebrated a religious ritual called Maha Puja Panghuni Uthiram Triruvila at the Palani Andawer Temple, Gampong Keudah, Kuta Raja District, Banda Aceh City. The religious procession received widespread attention from the majority Muslim Banda Acehnese, so they came in droves to witness the ritual up close. The formulation of the problem is to find out how the form and level of participation of the Muslim community in Banda Aceh City in the celebration of the Panghuni Uthiram Ritual and what are the factors that encourage and prevent the Muslim community in Banda Aceh from participating in the celebration of the Panghuni Uthiram Ritual. To answer the problems that arise and the achievement of objectives, this research is a field study (Field Research), the method used in the preparation of this thesis uses qualitative and descriptive methods and for data collection is done by interviewing several respondents who are in accordance with the discussion, observation, and documentation. . Judging by the current phenomenon, both Muslim and non-Muslim communities in Gampong Keudah have been able to form a good participation in the celebration of the Panghuni Uthiram Ritual in Hinduism. The form of participation that occurs in Gampong Keudah is in the form of personnel participation. This happens because energy is considered the easiest and most effective form of participation. The participation of energy also prevents the Muslim community from directly interacting with the Panghuni Uthiram ritual celebration activities.